Karawitan Composition “Pancung” | Komposisi Karawitan “Pancung” - wayan ade; I Komang Sudirga (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Pancung musical artwork is a Karawitan art creation that is inspired by the phenomenon of natural beauty, especially the gurgling flow of water around the Pancung river which is decorated with rock carvings together with the sacred Beji temple environment. Along the river, which is located on the west part of Banjar Kebon Singapadu, has its own charms such as waterfalls, springs, natural cliffs and those that have been carved by local residents. This area is commonly known by local residents as Beji Pancung. Based on this natural phenomenon, there is an interest for the composer to transform this phenomenon into an innovative musical composition. The media used to support this idea is a set of Gamelan Gong Gede Saih Pitu with the addition of the angklung kocok (shake) instrument.The method of creation in this music uses the creative process approach of Alma M. Hawkins, namely exploration, improvisation, and formation. This composition is based on the Tri Angga structure, namely kawitan, pengawak, and pengecet. Each part in the structure describes the atmosphere and the phenomena of Pancung's natural beauty from upstream to downstream which can be observed through processing patterns in musical elements, such as melody, rhythm, tempo, harmony, and dynamics, as well as patet playing which is rich in additive nuances.